Validated analytical methodology for the simultaneous determination of a wide range of pesticides in human blood using GC–MS/MS and LC–ESI/MS/MS and its application in two poisoning cases. Issue 5 (September 2015) - Luzardo, Octavio P.; Almeida-González, Maira; Ruiz-Suárez, Norberto; Zumbado, Manuel; Henríquez-Hernández, Luis A.; Meilán, María José; Camacho, María; Boada, Luis D.
Abstract: Pesticides are frequently responsible for human poisoning and often the information on the involved substance is lacking. The great variety of pesticides that could be responsible for intoxication makes necessary the development of powerful and versatile analytical methodologies, which allows the identification of the unknown toxic substance. Here we developed a methodology for simultaneous identification and quantification in human blood of 109 highly toxic pesticides. The application of this analytical scheme would help in minimizing the cost of this type of chemical identification, maximizing the chances of identifying the pesticide involved. In the methodology that we present here, we use a liquid–liquid extraction, followed by one single purification step, and quantitation of analytes by a combination of liquid and gas chromatography, both coupled to triple quadrupole mass spectrometry, which is operated in the mode of multiple reaction monitoring. The methodology has been fully validated, and its applicability has been demonstrated in two recent cases involving one self-poisoning fatality and one non-fatal homicidal attempt. Highlights: Development of a methodology for the simultaneous quantification of 109 pesticides Validation of the analytical parameters for human whole blood Application to the identification of the pesticide involved in two real cases Semi quantitative application to matrixes other than blood